Pemberian Hak Atas Ruang Bawah Tanah: Perspektif Hukum Agraria - Suyanto Suyanto (LAW Proscientist: Journal of Law Profesional Scientist, 2023)
This research aims to examine the right to control the state and its authority in granting rights to underground space based on Law No. 11 of 2020 concerning Job Creation in conjunction with PP No.18 of 2021. The type of research is normative legal research using primary and secondary legal sources, the approach used is Legislation, Conceptual, and Philosophy. The results of the research are (1). PP No. 18 of 2021 is to implement the provisions of Article 142 and Article 185 of the Job Creation Law The definition of land including space above and inside the body is different from the definition in the legal regime of the Basic Agrarian Law (hereinafter abbreviated as UUPA), (2). The granting of rights to underground space is a new norm regarding the granting of land rights, previously the norm governing the granting of land rights was the UUPA which had granted rights to the land surface, (3). The new norm can lead to conflicts in agrarian law norms, namely differences between holders of aboveground space rights and holders of underground space rights when the norm is not synchronized with other regulations.